Beyond the canonical niche: how astrocytes carried neurogenic potential into the brain parenchyma - Fogli, Marco; Nato, Giulia; Peretto, Paolo; Buffo, Annalisa; Luzzati, Federico (Frontiers in Cell and Developmental Biology, 2026)
The cellular and molecular programs underlying neurogenesis are deeply conserved in metazoans. In vertebrates, neural progenitor and glial lineages converged within the astroglia lineage, which can alternate between stem cell activity and homeostatic states that support neuronal function. In mammals, astroglia migrated into the parenchyma, where they further diversified both between and within regions and specialized in homeostatic support, while only two restricted populations retained neurogenic activity in the ventricular-subventricular (V-SVZ) and subgranular zones. Nevertheless, parenchymal astroglia maintain a latent neurogenic potential that can be reactivated under specific conditions, engaging a program identical to that of niche astroglia. Despite this widespread potential, the regenerative capacity of the mammalian brain is highly reduced compared with non-mammalian vertebrates. The regionalization of the embryonic progenitors into domains of committed progenitors is preserved in adult vertebrates, but while non-mammalian vertebrates continue to generate the same neuron types, in mammals, periventricular domains constituting the V-SVZ converge to generate olfactory bulb interneurons. Cortical and striatal astrocytes also converge toward related neuronal identities, resembling a population of transient developmental neurons. Thus, when astroglia colonized the parenchyma, they carried the niche with them, but their neurogenic potential may have shifted from a reservoir for regeneration to one for plasticity. Paraphrasing Santiago Ramón y Cajal, it is for the science of the future to change, if possible, this harsh evolutionary choice.